(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current state of internet addiction using the CIAS scale and investigate the factors related to internet addiction among students of the Branch Campus Hanoi Medical University in 2025. Methods: A cross-sectional descriptive study on 415 students from the first to the sixth year at the Branch Campus Hanoi Medical University in 2025, from 12/2024 to 6/2025. Data were collected by guiding participants to complete a structured self-administered questionnaire. Binary logistic regression analysis was employed to examine the association between psychological distress and the risk of internet addiction. Results: 40.2% of students meet the diagnostic criteria for internet addiction according to the CIAS assessment scale. The statistically significant factors related to internet addiction are: economic difficulties, a history of substance abuse, hours spent on the internet, the purpose of internet use, and psychological distress. Conclusion: A large proportion of students were at risk of or met the diagnostic criteria for internet addiction. According to an analysis of related factors, excessive internet use may be associated with a higher risk of addiction and increased levels of psychological stress among students. As a result, support programs should be established to increase students’ awareness of the negative consequences of internet addiction.